2019
DOI: 10.3390/fishes4030045
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a Pool and Weir Fishway for Iberian Cyprinids Migration: A Case Study

Abstract: One of the movement barriers that fish populations must overcome for migration success in the upper basin of Tormes river (Salamanca, Spain) is a 20 m high dam. The design of its pool and weir fishway for potamodromous fishes (mostly Iberian barbel—Luciobarbus bocagei—and Northern straight-mouth nase—Pseudochondrostoma duriense) to overcome the obstacle was improved in 2013. The aim of this study was to assess the efficiency of the fishway using FDX passive integrated transponder (PIT)-Tags inserted into the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
(44 reference statements)
0
8
0
Order By: Relevance
“…Field studies highlighted the role of key environmental variables, such as flow and water temperature, as triggers of upstream fish migration [92], which typically occurs from spring to early-summer [95,100], which points out the need to conduct fishway studies preferably during this time frame. Another interesting result is that efficiency upon negotiating this type of fishways revealed to be size-related with larger fish displaying a higher efficiency and lower transit time for ascension, relative to smaller ones [42,96].…”
Section: Nofmentioning
confidence: 95%
See 1 more Smart Citation
“…Field studies highlighted the role of key environmental variables, such as flow and water temperature, as triggers of upstream fish migration [92], which typically occurs from spring to early-summer [95,100], which points out the need to conduct fishway studies preferably during this time frame. Another interesting result is that efficiency upon negotiating this type of fishways revealed to be size-related with larger fish displaying a higher efficiency and lower transit time for ascension, relative to smaller ones [42,96].…”
Section: Nofmentioning
confidence: 95%
“…Width of the surface notches ranged between 20 and 30 cm, with both studies aiming to compare the performance of a plunging vs. a streaming flow regime through the notches. The other two (50%) NOF studies were conducted in the field (Douro basin) and included a dual-entrance fishway with 23 pools (2.6 m × 1.6 m), slopes ranging 8.8%-9.8%, and a total flow of 395 L·s −1 [92] and a 46-pool high slope (16.3%) fishway, with a flow of 140 L·s −1 [96]. Orifice area in both fishways ranged 0.02 m 2 -0.06 m 2 and their arrangement (as well as those from the lab studies) was set as offset.…”
Section: Overview Of Conditions Testedmentioning
confidence: 99%
“…Because the sizes of the individuals vary slightly between these species, these differences in preference are likely associated with their swimming abilities. Our results indicate that flow velocity, regardless of fishway type, is more important than water depth and flow rate for many of the target fish species [83].…”
Section: Effects Of the Rock-ramp Fishwaymentioning
confidence: 71%
“…Those results are much higher than the mean international average rates (Noonan et al, 2011) for non-salmonid fish (21,1% average, 19-45% range). More recent studies on rheophic cyprinids in vertical slot or pool and weir fishways showed adjusted passage efficiency from 7.1% to 66.7% for barbel (Ovidio et al, 2017;Grimmardias et al, 2022) and 25% for the Northern Straight Mouth Nase (Pseudochondrostoma duriense) (Pedescoll et al, 2019). Among the eurytopic and the limnophilic species, roach, pike, Esox lucius, perch, Perca fluviatilis, tench, Tinca tinca and carp, Cyprinus carpio did not cross the fishway, but only a few were tagged and/or approached M 1 .…”
Section: Discussionmentioning
confidence: 98%